2019
DOI: 10.1097/md.0000000000015539
|View full text |Cite
|
Sign up to set email alerts
|

Single shot versus continuous technique adductor canal block for analgesia following total knee arthroplasty

Abstract: Background: An adductor canal block (ACB) provides recognized analgesia following total knee arthroplasty (TKA). This meta-analysis compared the single-injection ACB (SACB) with the continuous-injection ACB (CACB). Method: Relevant studies were searched from PubMed (1996–October 2018), Embase (1980–October 2018), and Cochrane Library (CENTRAL, October 2018). Four randomized controlled trials (RCTs), which compared SACB with CACB, were included in our meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…11 Studies have shown that continuous adductor canal block was superior to single shot. 12 Studies have shown that iPACK with adductor canal block showed better post op VAS score and better range of knee motion. 13 in our study we placed a catheter in adductor canal to give 0.25% of bupivacaine 20 ml 6 th hry on day 0 and 0.25% 10 ml 6 th hry on day 1 for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies have shown that continuous adductor canal block was superior to single shot. 12 Studies have shown that iPACK with adductor canal block showed better post op VAS score and better range of knee motion. 13 in our study we placed a catheter in adductor canal to give 0.25% of bupivacaine 20 ml 6 th hry on day 0 and 0.25% 10 ml 6 th hry on day 1 for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is not the first meta-analysis of RCTs comparing the efficacy and safety of SACB with CACB to get command of pain after TKA. However, the authors believe that this meta-analysis is more complete than the previous meta-analysis published by Zhang et al [ 51 ] Our study included 5 recent high-quality RCTs, [ 38 41 , 46 ] thus decreasing publication bias and statistical bias. We extract data more objectively, bringing about more precise conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…First, the research by Zhang et al included only 4 RCTs with a total of 322 patients. [ 51 ] The results showed that the patients who received CACB had a better efficacy in VAS scores at 48 hours (both of rest-VAS and mobilization-VAS) than those who underwent SACB. However, the SACB group had similar efficacy compared with the CACB group in terms of morphine consumption, time to first opioid request, range of motion, and VAS scores(both of rest-VAS and mobilization-VAS) at 24 hours and 48 hours, also without increasing the risk of complications and length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroup analysis showed the increased risks of each of these complications were only observed in particular subsets of patients, which suggests continuous FNBs may not be an independent or universal risk factor for all patients. Previous studies have failed to demonstrate a higher risk of DVTs associated with continuous FNBs than with single-shot FNBs [ 13 , 29 ]. Although the present study did not find a significant increase in the risk of PJI for patients receiving a regional nerve block, which was similarly seen by Kopp et al [ 30 ], there may be other factors that indirectly influence the risk of infections such as antibiotic timing, the type of anticoagulant prophylaxis, the use of a drain, and postoperative blood transfusion [ 31 ].…”
Section: Discussionmentioning
confidence: 99%